Public libraries’ services during a pandemic - Mansourian, Yazdan (Qualitative and Quantitative Methods in Libraries, 2020)
This paper explores a number of key roles that public libraries can play during a pandemic. The paper categorises the common approaches adopted by public libraries to deal with this kind of crisis into three main categories including: passive responses, active practice and proactive initiatives. The passive approach is the least beneficial option as its only benefit is a collaboration with other sectors of society to stop the spread of the disease. The active practice which is based on pre-planning and quick actions provides a number of helpful services for the community during the disaster such as providing online access to resources and turning a number of face-to-face services into virtual. The third approach which is based on innovation and creativity is the most appropriate attitude and provides valuable services for the community when they need them most. Finally, the paper presents a matrix to depict the reactions of public libraries to the pandemic considering three stages of crisis management. The paper concludes having a proactive initiative approach is the most effective policy that public libraries can adopt to enable them to face the challenge effectively and help people during the crisis. Using available and emergent technologies, fostering active engagement with the community, collaboration with crisis management authorities are among the important steps that these libraries take into consideration.